Adaptations of the antarctic bacterium Paenibacillus tundrae IMV B-7915 to copper (II) chloride exposure - S. Komplikevych; O. Maslovska; T. Moravska; I. Yarmoliuk; N. Biront; Y. Zaritska; S. Hnatush (Ukrainian Antarctic Journal, 2023)
Heavy metals are common in Antarctic habitats. However, the adaptations of Antarctic microorganisms to heavy metals are poorly understood. One of the mechanisms of toxicity of transition metals is the formation of free radicals which damage the cell macromolecules. In 2020, we isolated the bacteria Paenibacillus tundrae IMV B-7915 from a sample containing moss, soil, and underground parts of Deschampsia antarctica (Berthelot Islands, Maritime Antarctic). The aim of the study was to investigate the influence of copper (II) chloride on the specific growth rate, the content of products of free radical damage to lipids and proteins, the activity of antioxidant defense system enzymes, and the synthesis of extracellular polymeric substances in P. tundrae IMV B-7915. The bacteria were incubated for an hour in Tris-HCl buffer with 2–8 mM copper (II) chloride, then washed and inoculated into the tryptic soy broth. The bacteria were cultured for 72 hours. The content of copper in the cells was determined by atomic absorption spectrometry. The content of indicators of lipid peroxidation (diene conjugates, lipid hydroperoxides, thiobarbituric acid-reactive substances), oxidative modification of proteins (carbonyl groups in proteins), the activity of the antioxidant defense system enzymes (catalase, superoxide dismutase, glutathione peroxidase, glutathione S-transferase, glutathione reductase), total thiols, exopolymeric compounds (exopolysaccharides and proteins) were determined photometrically. Within an hour, cells accumulate 1.5–3.4 mg Cu/g of biomass, leading to a decrease in biomass accumulation and specific growth rate within 24 hours. In cells, copper ions induce free radical reactions of damage to cell macromolecules, reflected in the increase in the content of primary lipid peroxidation products and carbonyl groups in proteins. Cell division is inhibited. In response, P. tundrae IMV B-7915 cells activate efflux systems, as evidenced by a significant decrease in copper content during prolonged cultivation, and enzymes of antioxidant defense and synthesis of exopolysaccharides. The complex of the studied adaptation reactions ensures the detoxification of copper accumulated in cells, reflected in the restoration of the specific growth rate.